Exploring the Psychosocial Lived Experiences of Nurses During the Pandemic in Sarawak: A Hermeneutic Phenomenology Study - Ai Ling, Chen (Unimas Publisher, 2025)
Introduction: This study explores the psychosocial lived experiences of nurses caring for COVID-19 patients in Sarawak, Malaysia. It aims to understand the emotional landscape, social disconnection, adaptation and commitment amidst the pandemic. The unprecedented crisis placed immense pressure on nurses, requiring them to address both professional and personal challenges while ensuring quality patient care. Materials and Methods: This qualitative study employed Heidegger hermeneutic phenomenology to uncover the meaning embedded in nurses’ psychosocial lived experiences. Ten nurses working in the Infectious Disease ward at Sarawak General Hospital were purposefully selected. Data was collected through semi-structured interviews and analysed thematically to identify and interpret patterns within the narratives. The emerging themes were further examined through Van Manen’s four existential structures: lived body, lived time, lived space and lived other, offering a comprehensive lens for interpreting the nurses’ experiences. Results: Five key themes were identified: navigating the emotional and physical landscape of COVID-19 nursing care, experiencing social disconnection and isolation, adapting to workplace challenges, strengthening camaraderie in the healthcare environment, and upholding commitment and professionalism. Conclusion: The findings underline the significant psychological impact of the pandemic on nurses, emphasising the need for systemic improvements in healthcare policies, nursing education and mental health support. Strengthening resilience, encouraging teamwork and integrating crisis management training into nursing curricula are crucial steps. Additionally, prioritizing mental health support systems is essential to mitigate the long-term emotional burden on healthcare workers. This study provides beneficial information in relation to developing a more supportive and sustainable healthcare environment.